PELAKSANAAN PERJANJIAN PEMBIAYAAN MURABAHAH DI BAITUL MAAL WATTAMWIL (BMT) JAMI’US SHOGHIR DESA TERBIT KECAMATAN TAPUNG - Ulya Arif; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Islamic economic development in Indonesia, particularly in the banking world is increasingly progressing very rapidly and as has started glory. This can be seen at least from two aspects, namely the aspects of Islamic banking assets and regulation. Implementation of the jurisprudence muamalah murabahah financing which is to buy the first items to be purchased by the customer after prior agreement. Once the goods are purchased on behalf of the bank, then the goods are sold to customers with an acquisition cost plus a profit margin according to the agreement, the purchase can be made in cash or deferred, either in the form of installments or all at once at a particular time.This research is a sociological juridical law, the definition of socio-juridical research is approach is to look at in terms of legislation and the fact that occur in the field, in accordance with the formulation problems expressed by the writer. While the population and samples are parties related to the issues examined in this study, the data source used, primary data, secondary data, and the data tersier. Data collection technique in this study with interviews and a review of the literature.From the results of research by the author can be concluded that, first: implementation of murabaha financing agreement by using wakalah in Baitul Maal wat tamwil (BMT) Jami'us Shoghir not in accordance with Islamic principles, both: economic factors are the main factors which is an obstacle for customers to implement their obligations. The fall or drop in palm oil prices result in some customers' revenue shortfall that automatically make customers late or even not perform its obligations in paying installments.Keywords: Implementation - Agreements - Murabahah - Baitul Maal Wat Tamwil (BMT) Jami'us Shoghir.